Case Of Adult Learners And Work Satifaction Who's Behind Them? - Asaari, Muhammad Hasmi Abu Hassan; Kariau, Noorliza (Anadolu University, 2004)
Yearly the number of working adults registering under distance education program in various universities in the nation is on the upward trend.